Consumer Inertia and Dynamic Price Competition - Bartłomiej Wiśnicki (Gospodarka Narodowa. The Polish Journal of Economics)
The aim of this research is to study firms’ decisions about price and quality in a setting where consumers cannot fully evaluate products and must rely on anecdotal evidence to make choices. Additionally, consumers exhibit inertia, or an overattachment to past purchases, in their decision making. To analyse firms’ behaviour, we employ a 2 period price competition model in which firms can choose their product quality. Consumers are aware of prices but learn about product quality through experience and anecdotal evidence, which influence their choices according to a simple decision rule. We obtain analytical results in the form of a Nash equilibrium for pricing and quality strategies across various levels of consumer inertia and conduct comparative statics. Our findings suggest that inertia intuitively makes the market less competitive as firms gain monopoly power over attached consumers. However, inertia also intensifies competition for unattached consumers and encourages firms to enhance product quality. Consequently, in certain situations, inertia can reduce product prices and contribute to improved market welfare.